Dynamics Analysis of Flexible Manipulator Driven by SMA Spring - TENG Yajun, CHEN Wujun, YANG Tianyang, JING Zhongliang, LIU Wuji (Shanghai Jiaotong Daxue xuebao, 2021)
Combining the flexible robot driven by intelligent materials with the octahedral variable geometry truss system, and based on the theory of octahedral variable geometry truss system, a single flexible unit is designed and driven by parallel shape memory alloy (SMA) spring. The kinematic model is established by utilizing the geometric method. The kinetic energy, the elastic potential energy, and the gravitational potential energy of the flexible manipulator are analysed. The general dynamics equation is established based on the Lagrangian dynamics. The driving force of a single flexible element of SMA spring is calculated by utilizing MATLAB. Adams simulation is performed, and the calculation results are in good agreement with the theoretical calculation results. Finally, a prototype of the flexible control arm is built and the rotation angles at different currents are measured. Modeling and simulation methods are useful references for other types of robots.